The Frontier Boys in the Grand Canyon; Or, A Search for Treasure - Roosevelt, Wyn, 1870- (Salt Lake City, UT : Project Gutenberg, 2010)
"The Frontier Boys in the Grand Canyon; Or, A Search for Treasure" by Wyn Roosevelt is a novel written in the early 20th century. This adventurous tale follows the journey of three boys$1 (BJim, Jo, and Tom$1 (Bas they navigate the challenges of the Southwestern frontier, particularly their adventures in the Grand Canyon. The story is filled with excitement, danger, and the pursuit of treasure, as the boys face encounters with wildlife and hostile Native American tribes. The opening of the book establishes a lively and spirited atmosphere, highlighted by a race among the boys on their mustangs. They banter about their ponies and explore the terrain, which is filled with the potential for adventure. As they camp for the night, tension builds when they encounter a feral wolf, demonstrating the unpredictable dangers of their wilderness surroundings. With the guidance of Captain Graves, their mentor, the boys learn to navigate both the physical and interpersonal challenges of frontier life, priming them for the thrilling escapades that lie ahead in their quest for treasure and safety. (This is an automatically generated summary.)s
Release date is 2010-07-20
E-text prepared by Darleen Dove, Roger Frank, Mary Meehan, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Frontier and pioneer life -- Juvenile fiction; Grand Canyon (Ariz.) -- Juvenile fiction